PENGARUH PERMAINAN KARTU HURUF TERHADAP KEMAMPUAN MEMBACA ANAK KELOMPOK A DI TK AMANDA CIPTA MENANGGAL SURABAYA - Isabella Hasiana (incrementapedia, 2021)
This research is motivated by the lack of use of letter cards in learning in kindergarten, in this case to develop children's reading skills, it is very necessary to have interesting learning such as letter card games, because by using letter card games develop the ability of the right brain, can recognize letters easily, with letter cards children can learn while playing, so that children are not easily bored and bored, children in kindergarten Amanda are less developed reading skills because of that many children can not read, develop abilities reading children can help children in preparing themselves to enter elementary school, this can make it easier for children to read because children already know the basics. The purpose of this study was to determine whether there is an effect of the game of letter cards on the reading ability of group A children at TK Amanda Cipta Menanggal Surabaya. The method in this study is a quantitative research method using the type of Pre-Experiential Design in the form of One Group Protest-Postest Design. This quantitative research has 3 stages: pretest, treatment treatment and posttest. Data collection used is observation and documentation. The results of the study were that there was no effect of letter card games on the reading ability of group A children in Amanda Cipta Menanggal Kindergarten, this was evidenced from the pre-test and post-test data obtained using SPSS v.20 which showed that the sig value obtained was 0,21<0.05, then Ho is automatically accepted Ha is rejected.